Haptoglobin levels are influenced by Hp1-Hp2 polymorphism, obesity, inflammation, and hypertension in type 2 diabetes mellitus - Rodrigues, Kathryna Fontana; Pietrani, Nathalia Teixeira; Carvalho, Laura Machado Lara; Bosco, Adriana Aparecida; Sandrim, Valeria Cristina [UNESP]; Ferreira, Claudia Natalia; Gomes, Karina Braga (Elsevier B.V., 2019)
Background: Type 2 diabetes mellitus (T2DM) is an inflammatory condition associated to obesity and increased oxidative stress. Haptoglobin (Hp) is an acute phase reactant that scavenges extracorpuscular hemoglobin from circulation and prevents heme-iron oxidative damage. Objective: To assess the association between Hp levels and Hp1-Hp2 gene polymorphism and clinical and laboratory parameters in patients with T2DM. Methods: The study sample consisted of 102 T2DM patients and 62 controls. Hp plasma levels were measured using an ELISA assay, and Hp genotyping was performed using a specific two-step allelic polymerase chain reaction. Results: Hp levels were higher in T2DM patients as compared to controls (p = 0.005). T2DM patients with high blood pressure had higher Hp levels than patients without this comorbidity (p = 0.021). Obese T2DM patients had higher Hp levels as compared to obese controls (p = 0.009) and to non-obese T2DM patients (p = 0.003). The Hp1-Hp1 genotype was showed to be associated to T2DM according to additive (OR = 3.038, 95% CI 1.127-8.192; p = 0.036) and dominant model (OR = 0.320, 95% CI 0.118-0.839; p = 0.010), but Hp2 allele carriers contributed with higher Hp levels in T2DM as compared to controls. Waist circumference (p = 0.002), BMI (p = 0.001), and IL-6 (p = 0.012), and hs-CRP (p = 0.001) levels positively correlated with Hp levels in the T2DM group. Conclusion: These results suggest that Hp levels are influenced by Hp1-Hp2 polymorphism, obesity, inflammatory status, and high blood pressure in T2DM. (C) 2018 SEEN y SED. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Haptoglobin; Type 2 diabetes mellitus; Polymorphism; Inflammation; Obesity